Social networks, geographic proximity, and firm performance in Viet Nam - Emma Howard (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
This paper uses panel data to assess the relative importance of social networks and geographic proximity to micro, small, and medium enterprises in Viet Nam. The results suggest that a larger social network, and hiring employees mainly through social networks, are both correlated with higher value added per worker. The number of government officials and civil servants in a firm's network emerges as particularly important. When the quality of contacts is controlled for, firms with tighter social networks have, on average, higher value added per worker. The analysis of spatial networks reveals that firms with a lower percentage of customers and suppliers in the same district actually have higher value added per worker. The results suggest that for micro, small, and medium firms in Viet Nam, strong social networks are much more important than geographic proximity.
Keywords: L14; L20; D22; 330; social networks; geographic proximity; manufacturing firms; Viet Nam